Pengaruh Pelatihan dan Motivasi terhadap Kinerja Karyawan Tenun Ikat Bandar Kidul Kediri (Studi UD. Medali Mas) - Zahrotul Jannah; Dymas Yulia Putri Kusumaningtyas (Al-Muzdahir : Jurnal Ekonomi Syariah, 2021)
The development of increasingly advanced technology requires every company to look for quality human resources so that the company becomes the best. .To get quality human resources, a company must be able to provide situations and conditions that might improve the abilities and skills of employees. .in this case UD.Medali Mas provides skills for employees through providing training and providing encouragement through motivation . This study aims to answer, describe and analyze the formulation of the problem; 1) How is the effect of training on the performance of UD. Medali Mas weaving employees. .2) How is the influence of motivation on the performance of UD. Medali Mas weaving employees. 3) How is the simultaneous influence of training and motivation on the performance of UD.Medali Mas ikat employees.This type of research uses quantitative research methods with data collection using questionnaires, interviews, documentation. While the data analysis technique used was multiple regression test, T test and F test. The results of this study are 1). There is a positive effect of training on the performance of UD. Medali Mas weaving employees. Because based on the test which shows that the T count is 2.656 while the T table is 1.984. 2). .there is a positive influence of motivation on the performance of UD. Medali Mas ikat employees. This is because based on the test which shows that the T count is 2.306 while the T table is 1.984. 3). .The results of the simultaneous analysis showed that there was a positive and significant influence between the variables of training and motivation on the performance of the ikat weaving employees at UD. Medali Mas. With the calculated F result of 47,033 and the F table of 3,09